Sharing Economic Partnership on Online Transportation - Dodi Dermawan (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
The model sharing economy concept in online using transactions through the coordination of applications that are connected to the internet. The aims of this study were to explain the influence factors asymmetric information and transaction costs on the partnership relation in the online mode of transportation in Indonesia. This study applies PLS-SEM analysis to explore the phenomena that occur in online drivers. The results showed is a significant positive effect of the asymmetric information factor on the transaction cost factor. Then the transaction cost variable does not have a significant effect on the partnership relationship factor. While the information asymmetry factor has a significant effect on the partnership relationship. Asymmetric information that occurs related to transaction information, incentive information and sanction information. The implication of the asymmetry that occurs to the driver causes the driver to lose bargaining power as a partner. Although drivers have experienced an increase in income, their job security is very unstable. The role of the government is needed to oversee and provide regulations to reduce asymmetric information, balance the bargaining power of drivers and the sustainability of their jobs.